ANALYSIS OF THE PARTICIPATION AND SIGNIFICANT ASPECTS OF COMMERCIAL BANKS IN THE FUND MARKET - Mardonov Shaxriyor Xolmirzo o‘g‘li (Journal Park Publishing, 2023)
This article analyzes the participation of banks in the stock market and examines the financial capacity of commercial banks. In particular, their capitalization level, loan portfolio and deposit were analyzed. Also, the article highlights the opinions of foreign and local scientists on this matter, and the author formulates suggestions and recommendations on the topic.
Keywords: bank capitalization, commercial banks, credit operations, deposit, securities, stock market, regression, progression, investment, institutional investor.